2017
DOI: 10.3892/ijmm.2017.2850
|View full text |Cite
|
Sign up to set email alerts
|

Alterations in splenic function and gene expression in mice with depressive-like behavior induced by exposure to corticosterone

Abstract: Depressed patients present with increased cortisol levels and attenuated immune responses. However, little is known about the association between depression and the spleen, as this is the largest peripheral immune organ. In this study, we examined alterations in splenic function and gene expression in mice with depressive-like behavior, well as the expression of certain proteins in related pathways. A mouse model of depression was established with the use of corticosterone. Splenic function and histopathology … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 41 publications
0
8
0
Order By: Relevance
“…43,45,56,57 Our results are consistent with previous results showing chronic stress disrupts spleen morphology. [43][44][45][46][47]60 Although the spleen is a blood filter and fixation was conducted through the circulatory system, if altered spleen morphology affects filtration through the spleen to impact fixation quality, the result is the same-functional deficits contributing to fragmentation supports the determination that spleen dysfunction occurs following chronic stress.…”
Section: Discussionmentioning
confidence: 99%
“…43,45,56,57 Our results are consistent with previous results showing chronic stress disrupts spleen morphology. [43][44][45][46][47]60 Although the spleen is a blood filter and fixation was conducted through the circulatory system, if altered spleen morphology affects filtration through the spleen to impact fixation quality, the result is the same-functional deficits contributing to fragmentation supports the determination that spleen dysfunction occurs following chronic stress.…”
Section: Discussionmentioning
confidence: 99%
“…In the survival analysis, COL6A5 and COL18A1 were validated to be significantly related to overall survival of ESCC patients. Previous studies demonstrated that the COL6A5 expression was significantly associated with depressed behavior and atopic dermatitis (Söderhäll et al, 2007; Zhan et al, 2017), but no articles manifested its correlation with cancer. In addition, COL18A1 has been proved to be a promising biomarker for ovarian cancer and was possibly involved in the progression of bladder cancer (Fang et al, 2013; Peters et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Zhan et al, 2017) and brain(Ren et al, 2011) health from toxic chemicals and other stressinducing factors. Elevated LPO levels, in terms of MDA, in TZ-treated rats was reversed in all BE+TZ group rats, suggest that BE can reduce lipid peroxidation by increasing the activity of the antioxidant enzyme and improving the free radical clearance ability of the Effect of TZ and Broccoli extract treatment on brain biochemical stress.…”
mentioning
confidence: 99%